Health-Promoting Schools Project for Palestine Children's Oral Health - Lamis Abuhaloob; Poul Erik Petersen (Elsevier, 2023)
Objectives: The aim of this work was to assess the oral health outcome of a 2-year comprehensive school oral health programme based on school-health education combined with supervised toothbrushing using 1450-ppm fluoride toothpaste amongst schoolchildren in Palestine. Methods: A quasi-experimental study (2016-2018) recruited 3939 schoolchildren aged 5 to 6 years from 30 intervention schools (n = 2333) and 31 comparison schools (n = 1606). At baseline and postintervention, mothers and schoolteachers completed World Health Organization (WHO) self-administered questionnaires about oral health of children, oral health behaviour, and family factors. Of the initial participants 75.8 per cent took part in the follow up studies. In addition, 25 calibrated dentists examined dental caries of children according to WHO criteria. Trained teachers provided comprehensive oral health education to children in the classrooms and held regular oral health sessions for mothers. Children brushed their teeth with fluoride-containing toothpaste (1450 ppm fluoride). Student t-test and logistic regression were used in the statistical analysis of changes in dental health and related knowledge, behaviours, and attitudes (P < .05). Results: In both dentitions, dental caries experience declined over the project. The reduction in Decayed, Missing and Filled permanent Teeth and Decayed, Missing and Filled Surfaces in permanent teeth was 23.3% and 23.2% (P < .001), respectively. The drop in caries experience indices in the Gaza Strip was 8 to 4 times higher than in West Bank, and it reached 47.4% reduction. Mothers and teachers showed improvement in positive knowledge and attitudes towards dental care. Involvement of schoolteachers in oral health in schools and acceptance of dental health education materials significantly enhanced oral health behaviour of children. Conclusions: The project recommends national implementation of an intervention for the improvement of oral health of schoolchildren and their parents in conflict zones. The project shows the importance of the WHO Health Promoting Schools concept and involving classroom-based health education carried out by schoolteachers. It is suggested to explore the health care system's capacity in hosting effective oral health programme and maintain its efficacy.